Double-suspension multi-functional equipment and devices for carrying children - JIN YANDONG (2017)
The invention relates to double-suspension multi-functional equipment and devices for carrying children. The double-suspension multi-functional equipment and devices comprise a vehicle frame, wheels mounted on the vehicle frame and a sitting and lying device used for allowing an infant to sit and lie down. The sitting and lying device is provided with a limiting device. The limiting device can limit relative rotation of a first seat support and a second seat support when the first seat support and the second seat support rotate to be in a plane. The sitting and lying device is provided with two disassembling openings, the two sides of the sitting and lying device are each hinged to the vehicle frame through one connecting rod assembly, and the vehicle frame comprises a first vehicle frame body and a second vehicle frame body which are hinged to each other. According to the sitting and lying device, one end of the first seat support, a seat left-inner connecting rod, a seat left-outer connecting rod and one en